Diagnostic utility of LEF1 and β-catenin in WNT pathway tumors with CTNNB1 mutation - Can Li; Lingdan Dong; Li Zhu; Wenbin Guan (World Journal of Surgical Oncology)
Abstract Objective This study aimed to compare the expression of lymphoid enhancer factor 1 (LEF1) and β-catenin in basal cell adenoma (BA), desmoid-type fibromatosis (DF), and pancreatic solid pseudopapillary neoplasm (SPN) to evaluate their diagnostic utility in tumors associated with the WNT/β-catenin signaling pathway harboring the mutation of CTNNB1 gene 3 exon. Methods Eighty tumor patients, including 26 BAs, 30 DFs, and 24 SPNs, were analyzed. Immunohistochemical staining was identified positive (nuclear staining of LEF1 and β-catenin in > 50% of tumor cells). The diagnostic rate of LEF1 alone, β-catenin alone, and their combination were compared for each tumor type and all patients. Results Compared to β-catenin, when LEF1 alone was used for diagnosis, the diagnostic rate increased by 46.16% for BA, 16.67% for SPN, and 11.25% for all patients, but decreased by 23.34% for DF. The combined use of β-catenin and LEF1 significantly increased the diagnostic ratio in BA (46.16%), SPN (16.67%), and all patients (21.25%), but only marginally in DF (3.33%). In terms of all WNT pathway tumors with CTNNB1 gene mutation encompassed by our study, statistical analysis revealed no significant difference between LEF1 alone and β-catenin alone. However, their combined application was highly significant (P = 0.001) . Conclusion While β-catenin is commonly used as a marker for WNT pathway tumors, its variable expression and localization can be challenging for diagnosis. Our study emphasizes the importance of LEF1 as a complementary marker to β-catenin in diagnosing BA, DF, SPN, and other WNT pathway tumors activated by exon 3 CTNNB1 gene mutation. The combined use of LEF1 and β-catenin enhances diagnostic accuracy and may help the identification of these tumor types.